Study of proximal femoral locking compression plate in extra capsular fracture neck of femur - G.O., Ravi; Saheb, Shaik Hussain (International Journal of Research in Medical Sciences, 2017)
Background: The hip joint transmits weight several times that of the body weight particularly during running, functioning as both a highly mobile and very stable joint. In weight bearing the pressure forces are transmitted to the head and neck of the femur at an angle of 1650 to 1700, regardless of the position of pelvis. The planes of force coincide with strongly developed trabeculae. The reacting force normally runs perpendicular to the cartilaginous epiphyseal plate. The mechanism of bone failure in a structure will fail if it suffers an overload situation. An overload situation will occur if the system is unable to absorb the energy that is applied to it. In the hip joint area this overload situation can occur as a result of number of independent but often interrelated factors. The present work is conducted to study the; profiles of patients with extra capsular fracture neck of femur, efficiency and outcome of fractures treated with Proximal Femoral Locking Compression Plate (PFLCP), intra - operative & post-operative complication following management of extra capsular fracture neck of femur with Proximal Femoral Locking Compression Plate. Methods: This is a prospective study of 21 cases of extra capsular fracture neck of femur admitted to Victoria and Bowring and Lady Curzon Hospitals, Bangalore, treated with PFLCP. Results: In our study of 21 cases, cases 13 cases were intertrochanteric fracture and remaining 8 were subtrochanteric fracture with the mean age was 51.47 years. Minimum age was 19 years and maximum age was 85 years. 14 patients (67%) were males and 7 patients (33%) were females, 13 IX patients (62%) had right-sided fracture and 8 patients (38%) had left-sided fracture. with right side being more common side affected. The average duration of stay in the hospital was 25.31 days. The average follow up was 18 months [11 to 23 months]. Out of 21 patients in our study 16 patients (76%) are able to sit cross-legged and can squat on ground without any problem. The functional results were graded according to Harris Hip Scoring, In our study, 10 patients (48%)had excellent results, 8 patients (38%)had good results, 2 patients (10%)had poor result, and 1 failed case (5%) as she is an elderly female of 85 years with limited activity both preoperatively due to physiological age and general weakness. Conclusions: In conclusion the potentiality of the Proximal Femoral Locking Compression Plate (PF-LCP) in varied indications, shows its versatility. Although not free of complications our study has demonstrated excellent results. The procedure offers, faster mobilization, rapid return to activities of daily living, improves the quality of life and gave a long term solution in patients with extracapsular fracture neck of femur. Larger studies with longer follow up will further validate the procedure.